2010
DOI: 10.4049/jimmunol.0903458
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Level Defines Two Functionally Distinctive Stages of Inflammatory Dendritic Cell Development from Mouse Bone Marrow

Abstract: Reactive oxygen species (ROS) have been implicated in various physiological activities. However, their role in dendritic cell (DC) activation and generation has not been investigated. Using the bone marrow-derived GM-CSF–induced ex vivo DC model, we characterize how induction of ROS correlates with inflammatory DC functionality and expansion. We describe that the functionality of GM-CSF–induced DCs is distinct in two developmental stages. Whereas division of DC-committed hematopoietic progenitor cells (HPCs) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…In a previous report, we showed that the differentiation process of peripheral blood monocytes to DC requires growth factor dependent production of intracellular Reactive Oxygen Species (ROS) (Del Prete et al, 2008; see also Sattler et al, 1999;Sheng et al, 2010). As revealed by ultrastructural analysis, DC exhibited an increased number of condensed mitochondria compared to monocyte precursors.…”
Section: Introductionmentioning
confidence: 85%
“…In a previous report, we showed that the differentiation process of peripheral blood monocytes to DC requires growth factor dependent production of intracellular Reactive Oxygen Species (ROS) (Del Prete et al, 2008; see also Sattler et al, 1999;Sheng et al, 2010). As revealed by ultrastructural analysis, DC exhibited an increased number of condensed mitochondria compared to monocyte precursors.…”
Section: Introductionmentioning
confidence: 85%
“…They are comparable, if not better, to the GM-CSF + IL-4 equivalents. These early GM-CSFderived DCs express lower levels of activation markers than early GM-CSF + IL-4-derived DCs, however as we demonstrate herein, these early DCs derived from GM-CSF cultures rapidly increased the expression levels of CD80, CD86 and MHCII upon LPS and CpG stimulation [14,16], and are capable of secreting cytokines and chemokines after stimulation. In addition, these early GM-CSF-derived DCs, like the early GM-CSF + IL-4-derived DCs, can stimulate T-cell proliferation after exposure to LPS.…”
Section: Introductionmentioning
confidence: 48%
“…We have shown that the early GM-CSF derived DCs are fully functional in terms of endocytosis, up-regulating activation markers upon TLR stimulation [14,16]. They are comparable, if not better, to the GM-CSF + IL-4 equivalents.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations